Complementary Model In Interaction Between Political Officials And Bureaucrats In Indonesia - Deddy S. Bratakusumah (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2017)
The relationship between politics and the bureaucracy or the political influence of the bureaucracy is a discourse that also surfaced in Indonesia. Various laws aremade to realize the Indonesian bureaucracy that is free from political influence. In fact, a complementary interaction between political officials and bureaucrats is anecessity in a bureaucratic system contained in Indonesia. The influence or control of political officials should be carried out within the framework of supervising the implementation of policies that have been decided in the political process and provide corrections to bureaucrats when finding errors or irregularities.